Integração financeira no mercado de ações - Piveta, Leonardo Berteli (Universidade do Vale do Rio dos Sinos, 2014)
This dissertation investigates the existence of integration in the stock Exchange market as well as it measures the changes that the subprime crisis may have caused in the relations between the emerging markets of Latin America and Central and Eastern Europe. In order to carry out this study, eleven stock exchange indexes of these markets were selected and the GARCH models and stochastic volatility were used. The results indicated the existence of financial integration between countries; furthermore, they suggested that the crisis has intensified these relationships.
Keywords: Emergentes; Mercados de ações; Crise financeira; Integração financeira; Modelos GARCH; Volatilidade estocástica; Emerging; Stock markets; Financial crisis; Financial integration; GARCH models; Stochastic volatility; ACCNPQ::Ciências Sociais Aplicadas::Economia